Variant-specific antibody profiling for tracking SARS-CoV-2 variant infections in children and adolescents - Kuthning, Daniela; Raafat, Dina; Holtfreter, Silva; Gramenz, Jana; Wittmann, Nico; Bröker, Barbara M.; Meyer-Bahlburg, Almut (Frontiers in Immunology, 2024)
Monitoring the seroprevalence of SARS-CoV-2 in children and adolescents can provide valuable information for effective SARS-CoV-2 surveillance, and thus guide vaccination strategies. In this study, we quantified antibodies against the spike S1 domains of several SARS-CoV-2 variants (wild-type, Alpha, Delta, and Omicron variants) as well as endemic human coronaviruses (HCoVs) in 1,309 children and adolescents screened between December 2020 and March 2023. Their antibody binding profiles were compared with those of 22 pre-pandemic samples from children and adolescents using an in-house Luminex®-based Corona Array (CA). The primary objectives of this study were to (i) monitor SARS-CoV-2-specific antibodies in children and adolescents, (ii) evaluate whether the S1-specific antibody response can identify the infecting variant of concern (VoC), (iii) estimate the prevalence of silent infections, and (iv) test whether vaccination or infection with SARS-CoV-2 induce HCoV cross-reactive antibodies. Both SARS-CoV-2 infection and vaccination induced a robust antibody response against the S1 domain of WT and VoCs in children and adolescents. Antibodies specific for the S1 domain were able to distinguish between SARS-CoV-2 VoCs in infected children. The serologically identified VoC was typically the predominant VoC at the time of infection. Furthermore, our highly sensitive CA identified more silent SARS-CoV-2 infections than a commercial ELISA (12.1% vs. 6.3%, respectively), and provided insights into the infecting VoC. Seroconversion to endemic HCoVs occurred in early childhood, and vaccination or infection with SARS-CoV-2 did not induce HCoV S1 cross-reactive antibodies. In conclusion, the antibody response to the S1 domain of the spike protein of SARS-CoV-2 is highly specific, providing information about the infecting VoC and revealing clinically silent infections.